2017
DOI: 10.1186/s40608-017-0148-2
|View full text |Cite
|
Sign up to set email alerts
|

Urinary biomarkers as indicator of chronic inflammation and endothelial dysfunction in obese adolescents

Abstract: BackgroundObesity is a pro-inflammatory state that may predispose patients to acute coronary syndrome characterized by chronic low grade inflammation resulting in endothelial dysfunction (ED). The aim of the study was to evaluate urinary biomarkers of inflammation and ED in adolescents with obesity.MethodsSixty three subjects were recruited for the study. Twenty healthy adolescents with normal body mass (NW), 14 overweight (OW), 29 obese (OA) subjects were selected. An EndoPat 2000 device was used to measure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 35 publications
2
27
2
Order By: Relevance
“…[15][16][17] The increase in the body weight and abdominal fat increases oxidative stress, inflammation processes, dyslipidemia, hypertension, insulin resistance/diabetes, cardiovascular diseases, and the complications of these conditions that are directly linked to the morbidity and mortality. [11,[18][19] On the other hand, the atherogenic process is a phenomenon that occurs slowly and may start years before the clinical manifestation. For this reason, many researchers are motivated to study and develop new therapeutic approaches, such as the use of plants that may improve the risk factors before the atherosclerotic process becomes an irreversible condition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[15][16][17] The increase in the body weight and abdominal fat increases oxidative stress, inflammation processes, dyslipidemia, hypertension, insulin resistance/diabetes, cardiovascular diseases, and the complications of these conditions that are directly linked to the morbidity and mortality. [11,[18][19] On the other hand, the atherogenic process is a phenomenon that occurs slowly and may start years before the clinical manifestation. For this reason, many researchers are motivated to study and develop new therapeutic approaches, such as the use of plants that may improve the risk factors before the atherosclerotic process becomes an irreversible condition.…”
Section: Discussionmentioning
confidence: 99%
“…The release of inflammatory cytokines and other markers such as Interleukin-1β (IL-1 β ), IL-6, Tumor Necrosis Factor-α, and C-reactive protein may also be reversible. [11,[20][21][22] The Elevated Plus Maze (EPM) test is widely used to investigate the psychological bases of anxiety. Usually an animal without any treatment tends to remain for a longer time in the closed arms that represents an exposition to naturally threatening situations, which in the The presence of substances that reduce anxiety makes the animal feel calmer and consider the environment less threatening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethnicity and sample size differences may have also contributed to the different results. The aforementioned study by Singh et al (2017) investigating urinary biomarkers in adolescents found a tendency for IL-6 to be higher in the urine of obese subjects but this increase was not significant. However, a significant positive correlation was reported between urinary IL-6 and TNF-α, another marker that was significantly elevated in obese adolescents (Singh et al, 2017).…”
Section: Interleukin-6 (Il-6)mentioning
confidence: 89%
“…Similarly, serum TNF-α is significantly increased in obese children compared to controls (Giordano et al, 2011). A recent study investigating urinary biomarkers in relation to BMI status among adolescents aged 10 to 20 years found that urinary TNF-α was significantly elevated in those who were obese (Singh et al, 2017). Increased urinary TNF-α may therefore be a potential noninvasive way of detecting obesity-related inflammation.…”
Section: Tumour Necrosis Factor-α (Tnf-α)mentioning
confidence: 99%